The political economy of state patronage of religion: Evidence from Thailand - Larsson, Tomas (International Political Science Review)
Deciding the character and level of official patronage of religion are fundamental questions for all states. Yet we know next to nothing about the determinants of such patronage. Are democratic governments more or less inclined than autocratic ones to seek legitimacy through religious patronage? Is it ultimately ideological struggles that determine the extent of government backing of religion? This article addresses these questions through an analysis of the evolution of the state$1 (Bs role as patron and protector of Buddhism (and other officially recognized religions) in Thailand. Specifically, it examines changes in government expenditure on Thailand$1 (Bs religious bureaucracy from 1960 to 2016. It finds that democratization and ideological struggles have been the main drivers of a significant expansion of government spending on religious patronage. - Reproduced. s